Development of Google Classroom Learning Management System-Based Mathematics Learning on Relations and Functions in Junior High School - Miftahul Atiqoh; M Farhan Ainun Ihsani; Ulfah Zulaikha; Budi Murtiyasa (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2026)
This study develops a Google Classroom–based learning management system (LMS) for Relations and Functions in junior high school and examines its feasibility. The study used an R&D approach with the ADDIE model involving eighth-grade students and a mathematics teacher at SMP Muhammadiyah 5 Surakarta. Data were collected through observation, interviews, expert validation, and user-response questionnaires, and analyzed quantitatively and qualitatively. The results show high validity (material expert 93%; media expert 87%) and high feasibility (students 91%; teacher 97%). The novelty lies in a complete and structured LMS learning flow for Relations and Functions, integrating mapped topics, tiered activities, quizzes, discussions, and assignments supported by tools such as Quizizz, YouTube, GeoGebra, and Google Forms. Pedagogically, the LMS supports systematic concept learning, student engagement, and formative feedback in one coherent environment.